Kontroversi Nilai Kesaksian Perempuan - Nasution, Khoiruddin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
Majority of conventional scholars almost never questioned of status of women's testimony stated Al-Baqarah (2): 282, that the testimony of women is only a half of that men. However, majority of contemporary scholars have different view. They argue that what has been stated in the verse has to be interpreted contextually. The paper tries to describe the different view of the conventional and contemporary scholars, why it happens, and what kind of interpretation seems to be suitable for nowadays. What have been found is that the different opinion between conventional and contemporary scholars appears seems to be due to different context and method of interpretation. Conventional scholar more textual in interpretation while contemporary one more contextual. This different method happens due to the different demand. The conventional scholar was able to apply easily and no difficulty what is stated in Al-Baqarah (2): 282 without cantextualization, while contemporary scholars need context. Moreover, applicable conceptand it is more guarantee justice for nowadays is that the testimony of men in general manner is equal of that woman. Since, generally speaking, men and women play equal role in all aspect of life; family, society and state. The conclusionis found by using contextual approach and put nomative-universal nash more and before pratice-temporal. nash, while Al-Baqarah (2): 282 is included in practice-temporal nash. In another words, what has been stated in al-Baqaroh (2):282 is more contextual than normative. Therefore, different context automatically produces different concept.